Tuberculous Otomastoiditis on High-Resolution Temporal Bone CT: Comparison with Nontuberculous Otomastoiditis with and without Cholesteatoma - Rho, M.H.; Kim, D.W.; Kim, S.S.; Sung, Y.S.; Kwon, J.S.; Lee, S.W. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: Our purpose was to evaluate the differential findings of tuberculous otomastoiditis (TOM) and nontuberculous chronic otomastoiditis with or without middle ear cholesteatoma on high-resolution CT of the temporal bone.MATERIALS AND METHODS: We reviewed 19 cases of TOM, 30 cases of chronic otomastoiditis (COM), and 30 cases of COM with cholesteatoma (CHOM), all of which had been confirmed by pathologic examination after surgery or middle ear mucosal biopsy. Two neuroradiologists analyzed the findings of temporal bone CT.RESULTS: The soft tissue attenuation in the entire middle ear cavity, preservation of the mastoid air cells without sclerotic change, and soft tissue extension to the external auditory canal (EAC) or mucosal thickening of the bony EAC, had statistical significance (χ2 test, P < .05) between the TOM group and the COM group and between the TOM group and the CHOM group. Erosion of the ossicles and scutum was statistically significant (χ2 test, P < .05) between the TOM group and the CHOM group.CONCLUSION: Findings of soft tissue in the entire middle ear cavity, preservation of mastoid air cells without sclerotic change, soft tissue extension, or mucosal thickening of the EAC with intact scutum seemed to be helpful in differentiating TOM from COM and CHOM.